2017
DOI: 10.1177/0258042x17707659
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Sustainability Performance and Financial Performance: Empirical Evidence from Japan and India

Abstract: Purpose The purpose of this article is to explore the disclosure of corporate sustainability (CS) practices and to examine the association between sustainability performance and financial performance in Asian context considering firms from India and Japan. Design/methodology/approach The present study is based on secondary data collected from annual reports and CS reports of 28 and 35 listed non-financial firms from India and Japan from 2009 to 2014. Content analysis (binary coding system) is employed to calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 42 publications
(62 reference statements)
4
23
0
4
Order By: Relevance
“…Accordingly, Haninun et al (2015); Stefan & Paul (2008); King & Lenox (2001); Konar & Cohen (2001); Russo & Fouts (1997) observed a liaison between environmental performance and financial performance and found that it pays to be green. Laskar et al (2017) using a sample of 28 listed non-financial firms from India and 35 from Japan examined the alliance amid sustainability performance and financial performance. Using regression model, study found positive significant impact of sustainability performance on financial performance for both the nations.…”
Section: Review Of Literature and Hypotheses Developmentmentioning
confidence: 99%
See 3 more Smart Citations
“…Accordingly, Haninun et al (2015); Stefan & Paul (2008); King & Lenox (2001); Konar & Cohen (2001); Russo & Fouts (1997) observed a liaison between environmental performance and financial performance and found that it pays to be green. Laskar et al (2017) using a sample of 28 listed non-financial firms from India and 35 from Japan examined the alliance amid sustainability performance and financial performance. Using regression model, study found positive significant impact of sustainability performance on financial performance for both the nations.…”
Section: Review Of Literature and Hypotheses Developmentmentioning
confidence: 99%
“…For this research, environmental performance is employed as independent variable (Haninun et al, 2018;Laskar et al, 2017;Manrique & Marti-Ballester, 2017;Chang, 2015;Nakao et al, 2007). To measure environmental performance, variables viz.-a-viz.…”
Section: Measurement Of Environmental Performancementioning
confidence: 99%
See 2 more Smart Citations
“…Standardization frameworks provide confidence that reports are auditable when reports claim to adhere to a certain standard. The GRI reporting framework, recognized as the most common standard for corporate sustainability reporting, is increasingly espoused by corporations headquartered in developing and developed countries alike, but the activity levels of different industries are unalike due to the engagement activities being different themselves (Laskar, Chakraborty, & Maji, ). As the most utilized initiative in the field of corporate sustainability reporting, the GRI coins the term “external assurance” for an array of approaches to evaluate reporting regarding sustainable development (Sukhonos & Makarenko, ).…”
Section: Literature Reviewmentioning
confidence: 99%